EFL Students’ Attitudes Toward Online Learning in Speaking Classes: A Case Study of Semester VI Students at The Faculty of Languanges and Arts - Murni Murni; Jelita Purnama Sari; Mira Mailani; Stefani Angelica Sinambela (Faculty of Tarbiyah nad Teacher Training, 2026)
This study investigates EFL students’ attitudes toward online learning in speaking classes among Semester sixth students at the Faculty of Languages and Arts.The research focuses on students’ cognitive beliefs, affective feelings,and behavioral responses toward the implementation of online learning platforms in speaking activities.The study also explores the factors influencing students’ attitudes and examines how these attitudes relate to their speaking participation and confidence.This research employed a qualitative case study design.The participants were sixth-semester students from the English and Literature Department at the Faculty of Languages and Arts.The data were collected through questionnaires and interviews,The collected data were analyzed descriptively by identifying students’perceptions,emotional experiences, and participation in online speaking classes.The findings revealed that most students showed positive attitudes toward online learning in speaking classes.Students believed that online learning provided flexibility,easier access to learning materials,and a more comfortable environment for practicing speaking skills.Many students also reported feeling less nervous and more confident when speaking through online platforms because they did not face direct classroom pressure.However,several challenges were still found, such as unstable internet connections, limited interaction,technical problems,and difficulties in maintaining active participation during online learning.Despite these obstacles,online learning was considered helpful in supporting students’ speaking confidence and engagement in speaking activities.The study concludes that students’ attitudes play an important role in determining the effectiveness of online learning in speaking classes.Positive attitudes can encourage greater participation and improve students’ confidence in speaking English.